New-age elderly in Germany - how to live better with healthy experiences - Loureiro, S. M. C.; Sarmento, E. M.; Middendorf, J. (Revista Turismo e Desenvolvimento/Journal of Tourism and Development, 2017)
This study aims to analyze which potential attributes of anti-ageing experiences (goods, services, and experiences) will tend to be associated with subjective happiness; how cognitive age is associated with mindfulness and the influence of mindfulness on subjective happiness. Senior universities were contacted and approached by the research team to conduct the study. The goals of this study were explained to the managers of the senior universities and the survey collected among the people who participate in the activities and are enrolled in the senior universities. To analyze this theme over two hundred (250) questionnaires were distributed during January 2016 in Hamburg. The findings reveal that (i) mindfulness tend to have a positive effect on subjective happiness among elderly consumers, (ii) cognitive age and chronological age are not overlapped and (iii) the way elderly consumers perceive the anti-aging products and experiences may be correlated with subjective happiness.